THE INTERRELATIONSHIP BETWEEN CHANGES IN IMMUNE AND BIOCHEMICAL INDICATORS IN AUTOIMMUNE LIVER DISEASE - Kurbonova Z.Ch; Tairova G.B.; Sayfutdinova Z.A. (The Bioscan, 2025)
Significant hypergammaglobulinemia and the presence of many autoantibodies in the blood are symptoms of autoimmune hepatitis, a chronic liver illness with an unclear etiology that is characterized by periportal or more widespread inflammation. Current theories about the pathophysiology of AH include the interplay of genetic predisposition, immunological tolerance abnormalities, and environmental variables. The liver develops progressive non-inflammatory and fibrotic alterations as a result of this interaction, which triggers T-cell immune responses against hepatocyte antigens. With an annual incidence of 0.1–1.9 cases per 100,000 and a frequency of 3–17 instances per 100,000 in both Europe and the US, AH is regarded as a rather uncommon disease. Therefore, it is estimated that there are between 10,000 and 20,000 of these patients in the Russian Federation. KEYWORDS: ALT, AST, immunoblot analysis, Liver-9-Line, membrane enzyme immunoassay, IgG autoantibodies, AMA-M2, Sp100, gp210, SLA/LP, LKM-1, LC1, F-actin, actinin, tropomyosin